2021
DOI: 10.1016/j.jinf.2021.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Covid-19 organizing pneumonia in critically ill patients

Abstract: Outcomes of Covid-19 organizing pneumonia in critically ill patients Dear editor,Efficacy of corticosteroids in COVID-19 pneumonia has been reported in numerous studies. 1 However, Yang et al. concluded that corticosteroids have a negative impact, suggesting that not all patients benefit from the therapy. 2 Features of organizing pneumonia (OP) have been observed in radiological and histopathological studies from these patients. [3][4][5] OP has usually a good response to corticosteroids. The possible correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…In that study, OP was observed in 4.8% of these patients, with significant radiological and clinical improvement following steroid administration (28). In addition, in a study on respiratory intermediate care unit patients, 58% of patients that underwent a chest CT scan had a radiological pattern consistent with OP and a significantly decreased need for intubation and in-hospital mortality compared to those with a GGO pattern (29).…”
Section: Discussionmentioning
confidence: 86%
“…In that study, OP was observed in 4.8% of these patients, with significant radiological and clinical improvement following steroid administration (28). In addition, in a study on respiratory intermediate care unit patients, 58% of patients that underwent a chest CT scan had a radiological pattern consistent with OP and a significantly decreased need for intubation and in-hospital mortality compared to those with a GGO pattern (29).…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, if the worst OSCI = 4, the odds for OP are 2.722 times higher than having OSCI ≤ 3. After adjusting for other factors, no differences were found between groups for sex, frailty score, comorbidities, and the use of dexamethasone as a treatment for COVID- [12,13]. Both studies suggested that a more severe disease may be associated with progression to OP.…”
Section: Resultsmentioning
confidence: 91%
“…In that study, 83% of the patients diagnosed with OP previously required supplementary oxygen during the pneumonia phase of COVID-19, and half of them required ICU admission with 46% requiring invasive mechanical ventilation. Contrarily, among critically ill patients with COVID-19 pneumonia, admitted to an ICU, Rocha et al.de scribed a prevalence of OP that reached 58.0% [ 12 , 13 ]. Both studies suggested that a more severe disease may be associated with progression to OP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of developing organising pneumonia after COVID-19 infection is not well established, but may be related to the severity of the initial COVID-19 infection. While one study showed that CT changes suggestive of organising pneumonia occur as early as 3 weeks after the onset of COVID-19 infection,12 in severe COVID-19 infection, the diagnosis of organising pneumonia is often reached via CT scan at time of the initial COVID-19 infection 13. Organising pneumonia following severe COVID-19 infection also presents primarily with hypoxaemia.…”
Section: Discussionmentioning
confidence: 99%